PEMAKAIAN JILBAB KREASI BARU DI KALANGAN MAHASISWI (STUDI KASUS TERHADAP MAHASISWI UNIVERSITAS NEGERI SEMARANG) - Mula Hela, Rofiul; Alimi, Moh Yasir (Solidarity: Journal of Education, Society and Culture, 2013)
The phenomenon of the veil now likely to lead to consumer behavior is characterized by the development of lifestyle. Veiled style among adolescents in particular, with the development of new creations hijab models to be very diverse. The attraction of individuals to wear the hijab headscarf with the development of new creations that vary a lot Semarang State University student to imitate and wear the hijab as a clothing model that is now said to be so out of date. Among female students who wear headscarves new creations were not always wear her hijab wherever she travels. This study attempts to answer the research problem is how the meaning of the State University of Semarang student of the veil of new creations. The study used a qualitative approach. In the analysis phase, authors use the theory of consumer behavior Jean P. Baudrillard and lifestyle concepts David Chaney. The results showed that most students make sense of the veil that she wears but to follow the rules of Islamic dress, were also influenced by the veil which follow fashion trend. Veil also for some students UNNES have the meanings not only as an obligation of a Muslim woman in a close the genitals but can interpret as an elegant dress, formal dress and modern. They wear the hijab was expanded to a modern life style headscarves and follow the trend that is popular in the community. So that the veil became a collection of hunting and result in consumer shopping behavior.